SOFKA AND MLADEN: TWO UNRELIABLE EXISTENCES: (Tragedy and Sacrifice in the novels Impure Blood and The Boss Mladen of Borisav Stanković) (Heritage, 2020)
Borisav Stanković (1876-1927) made with his novels a decisive step in the later stage of Serbian realism in the supremacy of the novel over the short story. Out of three novels he was writing and finished only one (Impure Blood), and the novel The Boss Mladen may be interpreted and analysed as the finished one. In our paper a female literary character of Sofka and Mladen, the main character of the novel The Boss Mladen, were observed simultaneously.  We concluded that Sofka had acted instinctively while Mladen rationally, but in the end the result had been similar: both characters had been defeated spiritually.
Keywords: B. Staković, tragically, victim, existence